Which expression is equivalent to the equation above

Accepted Solution

Answer: third optionStep-by-step explanation: The negative exponent rules establishes: [tex]a^{-n}=\frac{1}{a^n}[/tex] The power to power property establishes:[tex](a^b)^c=a^{bc}[/tex] The quotien of power property establishes that when you divide two powers with equal base you must subtract the exponents. Applying the properties, you obtain: [tex]\frac{(4p^{-4}q)^{-2}}{10pq^{-3}}}=\frac{q^3}{10(4p^{-4}q)^{2}}=\frac{q^3}{10p(16p^{-8}q^{2})}=\frac{p^8q^3}{160pq^2}=\frac{p^7q}{160}[/tex] Β